ENHANCING STRATEGIES FOR THE CONTROL AND MANAGEMENT OF ORAL DISORDERS IN INDIVIDUALS WITH CARDIOVASCULAR DISEASES - Muratova Saodat Kadirovna, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract: Cardiovascular diseases (CVDs) are among the leading causes of morbidity worldwide and are increasingly associated with oral inflammatory conditions, particularly periodontal disease. The bidirectional relationship between systemic inflammation and oral pathology highlights the need for updated preventive and therapeutic approaches in patients with CVDs. This study evaluates modern protocols for oral disease prevention and treatment in cardiovascular patients, considering their pharmacological background, risk factors, and altered physiological responses. Comprehensive analysis demonstrates that individualized prevention strategies, minimally invasive treatment methods, and strict infection control significantly reduce oral complications and systemic inflammatory burden. The findings emphasize the necessity of integrated dental–cardiological management to enhance patient outcomes.